I have been trying to verify the inequality for $x\geq k, y\geq k,$ and $k\geq 1,$ $\left(\frac{\left(x-k\right)}{x+1}\right)\left(\frac{\left(y-k\right)}{y+1}\right)+\left(\frac{\left(x-k\right)}{x+1}\right)+\left(\frac{\left(y-k\right)}{y+1}\right)\geq\left(\frac{\left(xy-k^2\right)}{xy+1}\right) . $ Let me show my attempt.

Let us try to prove $\left(\frac{\left(x-k\right)}{x+1}\right)\left(\frac{\left(y-k\right)}{y+1}\right)+\left(\frac{\left(x-k\right)}{x+1}\right)+\left(\frac{\left(y-k\right)}{y+1}\right)-\left(\frac{\left(xy-k^2\right)}{xy+1}\right)\geq 0 $

But the left hand side of the above inequality is equal to


$$=\frac{2x^2y^2-2kx^2y+k^2x-2kx-2kxy^2+2xy+2k^2xy-2kxy+x+2k^2-2k-2ky+y+k^2y}{\left(x+1\right)\left(y+1\right)\left(xy+1\right)}. $$

Is there anyway to conclude $2x^2y^2-2kx^2y+k^2x-2kx-2kxy^2+2xy+2k^2xy-2kxy+x+2k^2-2k-2ky+y+k^2y\geq 0$ using factorization or any other technique?

One can observe that whenever $k=1,$ $$2x^2y^2-2kx^2y+k^2x-2kx-2kxy^2+2xy+2k^2xy-2kxy+x+2k^2-2k-2ky+y+k^2y=2xy(x-1)(y-1)\geq 0$$ and the result is true whenever $k=1.$


I shall not mention the obvious symmetry.

What I did is to look at the minimum value of function $$f(x,y)=\frac{x-k}{x+1}\times\frac{y-k}{y+1}+\frac{x-k}{x+1}+\frac{y-k}{y+1}-\frac{x y-k^2}{x y+1}$$ $$f(k,y)=\frac{(k-1) (k-y)}{(y+1) (k y+1)}$$ Its derivative cancels at $$y_*=k+\frac{\sqrt{k^4+k^3+k^2+k}}{k}$$ and the second derivative test shows that this is a minimum.

Now, computing $$f(k,y_*)=\frac{2 k^2+k+1-2 \sqrt{k (k+1) \left(k^2+1\right)}}{1-k}$$ is never positive. It reaches a minimum value at $k=1+\sqrt 2$ and for such a value we have $-0.0470219$.

Just to be sure, I also computed the partial derivatives and set them equal to $0$. The problem is that this leads to $7$ solutions among which only two are explicit.

Running a few cases, it seems that the minimum effectively occurs at $x=k$ and $y=y_*$. So, to me the inequality does not hold.

I suggest you to do a contour plot of $f(x,y)$ for any $k$ of your choice and ask for the level $-0.01$. You will find here the case for $k=10$; the area on the left of or below the line corresponds to negative values of $f(x,y)$.


After comments, considering the inequality $$\frac{x-k}{x+1}\times\frac{y-k}{y+1}+\frac{x-k}{x+1}+\frac{y-k}{y+1}\geq \color{red}{K}\frac{x y-k^2}{x y+1}$$ the problem is to find $K$.

So, as before, I considered the function $$f(x,y)=\frac{x-k}{x+1}\times\frac{y-k}{y+1}+\frac{x-k}{x+1}+\frac{y-k}{y+1}- K\frac{x y-k^2}{x y+1}$$ then computed $f(x,x)$, assumed $x=k+\epsilon$, developed as a series. The constant term of the expansion is $$-2 (k+1)^2 \left(k^2+1\right) (k(k+1)K-(1+k^2))$$ making it equal to $0$ gives $$K=\frac{k^2+1}{k (k+1)}\implies f(x,x)=\frac{(k-x)^2 \,\,A}{k (k+1) (x+1)^2 \left(x^2+1\right)} $$ where $$A=(2 k^2+3 k-1)x^2+2 \left(k^2-1\right) x+(k-1) (2 k+1)$$ does not show any real root. So, $f(x,x) \geq 0$

  • $\begingroup$ Thanks. It appears that if the right hand side of the inequality is $\frac{1}{K} ((xy−k^2)/(xy+1)),$ the inequality might be true! $\endgroup$ – mathlover Apr 19 at 10:01
  • $\begingroup$ @mathlover. I suppose. Now, the problem is to find $K$. Cheers :-) $\endgroup$ – Claude Leibovici Apr 19 at 10:05
  • $\begingroup$ Great. Thanks for all the suggestions. $\endgroup$ – mathlover Apr 19 at 10:06
  • $\begingroup$ @mathlover. Have a look at the edit. $\endgroup$ – Claude Leibovici Apr 19 at 11:22
  • $\begingroup$ excellent modifications after comments. Thanks. $\endgroup$ – mathlover Apr 19 at 11:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.